2017
DOI: 10.3389/fnmol.2017.00408
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of Inwardly Rectifying Potassium (Kir) 4.1 Channels Facilitates Brain-Derived Neurotrophic Factor (BDNF) Expression in Astrocytes

Abstract: Inwardly rectifying potassium (Kir) 4.1 channels in astrocytes regulate neuronal excitability by mediating spatial potassium buffering. Although dysfunction of astrocytic Kir4.1 channels is implicated in the development of epileptic seizures, the functional mechanisms of Kir4.1 channels in modulating epileptogenesis remain unknown. We herein evaluated the effects of Kir4.1 inhibition (blockade and knockdown) on expression of brain-derived neurotrophic factor (BDNF), a key modulator of epileptogenesis, in the p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
39
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 38 publications
(47 citation statements)
references
References 67 publications
0
39
0
Order By: Relevance
“… 57 Astrocytic Kir4.1 channels are blocked by antidepressants and it was recently shown that small interfering RNA–mediated knockdown of Kir4.1 channels in cultured astrocytes is sufficient to increase BDNF expression. 58 However, direct effects of monoamines through their receptors on BDNF expression in astrocytes may not be ruled out just yet. It is shown that dopamine as well as norepinephrine induces BDNF expression in cultured astrocytes.…”
Section: Brain-derived Neurotrophic Factormentioning
confidence: 99%
“… 57 Astrocytic Kir4.1 channels are blocked by antidepressants and it was recently shown that small interfering RNA–mediated knockdown of Kir4.1 channels in cultured astrocytes is sufficient to increase BDNF expression. 58 However, direct effects of monoamines through their receptors on BDNF expression in astrocytes may not be ruled out just yet. It is shown that dopamine as well as norepinephrine induces BDNF expression in cultured astrocytes.…”
Section: Brain-derived Neurotrophic Factormentioning
confidence: 99%
“…Therefore, dysfunction of Kir4.1 channels elevates not only extracellular K + , but also glutamate levels at tripartite synapses (Ohno et al, 2015 ; Ohno, 2018 ). Furthermore, we recently demonstrated that inhibition (channel blockade or expressional suppression) of Kir4.1 channels facilitated the expression of brain-derived neurotrophic factor (BDNF) in astrocytes, which may produce diverse effects including synaptic plasticity, neural sprouting, neurogenesis and reactive gliosis in the brain (Kinboshi et al, 2017a ; Ohno, 2018 ).…”
Section: Introductionmentioning
confidence: 99%
“…Kir4.1 expression is significantly reduced in models of epilepsy (Ivens et al, ; Kinboshi et al, ; Nagao et al, ; Ohno, ; Zurolo et al, ) and after traumatic CNS injury (Olsen et al, ; Pivonkova, Benesova, Butenko, Chvatal, & Anderova, ; Stewart et al, ) but little is known regarding the underlying molecular mechanism contributing to Kir4.1 protein and mRNA reductions. We used a LiPilo model of SE to examine changes in Kir4.1 expression in the hippocampus during the development of epilepsy after a primary insult.…”
Section: Resultsmentioning
confidence: 99%